The Effects of Self-Pollination on Seed Development and the Process of Oil and Squalene Accumulation in Camellia oleifera - GU Xu; ZHANG Mei-hong; YAN Xin-long; LIU Zhuo-zhi; YANG Hong-yan (Liang you shipin ke-ji)
Camellia oleifera is a self-incompatible plant. This study examined the effects of self-pollination on seed development, and the accumulation of oil and squalene in seeds using Yunyoucha No. 4, which has been widely cultivated-in Yunnan Province. Under the self-pollination treatment, the size, fresh weight and oil content of fruits and seeds at different developmental stages were measured. Additionally, the fatty acid and squalene content in Camellia oil was analyzed, with the natural-pollination treatment serving as a control. The results showed that the development of fruits and seeds under self-pollination was later than that under natural-pollination. During the seed expansion stage, the size and fresh weight of fruits and seeds and oleic acid content in Camellia oil under self-pollination were significantly lower than those under natural-pollination. However, no significant differences were observed at the maturity stage. Differences in the oil and squalene content of self-pollinated seeds were significantly lower than those in natural-pollination from the seed expansion stage to the maturity stage. These findings suggested that self-pollination delayed fruits and seeds growth. The influence of self-pollination on the phenotypes of fruits and seeds as well as the accumulation of oil and squalene in Camellia oil mainly acted during the seed expansion stage. This study can provide valuable insights for the subsequent optimization of the high-yield technology in oil tea production.